Post-exercise Effects and Long-Term Training Adaptations of Hormone Sensitive Lipase Lipolysis Induced by High-Intensity Interval Training in Adipose Tissue of Mice - Liu, Yang; Dong, Gaofang; Zhao, Xiaobo; Huang, Zerong; Li, Peng; Zhang, Haifeng (Frontiers in Physiology, 2020)
Although studies have proven that high-intensity interval training (HIIT) shows a comparable effect to moderate-intensity continuous training (MICT) on reducing body fat, especially visceral fat, the mechanism is still unclear. Since MICT consumes more fat during exercise, the mechanism of HIIT weight loss may be related to post-exercise effects, long-term adaptive changes, and hormone sensitive lipase (HSL). The objective of this study was to compare the post-effects of acute exercise, long-term adaptive changes on HSL activity and catecholamine-induced lipolysis between HIIT and MICT. Following a 14-week high fat diet (HFD), obese female C57Bl/6 mice were divided into acute exercise groups (one time training, sacrificed at rest and 0, 1, 12 hours after exercise, n=49),-L groups (12-week long-term training, 12-hour fasting, n=21), and -C groups (12-week training, primary adipocytes were isolated and stimulated by catecholamine in vitro, n=18). MICT or HIIT treadmill protocols (running distance matched) were carried out during training. Comparison of acute exercise effects by two-way ANOVA showed no time×group interaction effect, however, a significant increase in HSL-Ser563 (at 0, 1 hour) and Ser660 phosphorylation (at 0, 1, 12 hours) in inguinal (subcutaneous) fat was only observed in HIIT mice (P<0.05 vs Rest), but not in MICT mice. The periuterine (visceral) fat HSL expression and phosphorylation of HIIT mice was similar to or lower than MICT mice. After long-term training, 12-hour fasting significantly increased periuterine fat Ser563 phosphorylation in HIIT mice (P<0.05), but there was no change in MICT mice. Under stimulation of catecholamine in vitro, isolated primary adipocytes from periuterine fat of long-term HIIT mice showed a higher Ser563 increase than that found in MICT mice (P<0.05). The quantity of triglyceride lipid bonds (representing lipolysis level) was significantly lower after HIIT than MICT (P<0.05). The results indicate that 1) acute HIIT can induce an increase of HSL phosphorylation in subcutaneous fat lasting at least 12 hours, implying longer post-exercise lipolysis than MICT. 2) Long-time HIIT has a better effect on improving catecholamine resistance of visceral adipocytes caused by a HFD, which allows fat to be mobilized more easily when stimulated.